An rGO-coated mn-ti co-doped sodium fluorophosphate material, a preparation method and application thereof

CN119419245BActive Publication Date: 2026-10-23SHUANGDENG GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411544519.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2026-10-23
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

[0003]聚阴离子型正极材料凭借其三维空间结构、低成本、高安全性等特质成为钠离子电池正极材料领域的研究热点,目前常见的钠离子电池正极材料仍面临能量密度低、循环性能差等诸多挑战

Benefits of technology

[0031](1)本发明通过在Na2FePO4F材料的基础上进行Mn-Ti共掺杂以及rGO包覆,提升磷酸盐材料的电子电导率,同时增强了材料的结构稳定性,使正极活性材料兼具较高的能量密度和循环稳定性;其中,锰掺杂能够通过有效提高材料的能量密度,并可在晶格间锚定以拓宽晶格尺寸,提高钠离子传输速率;低价钛的掺杂能够稳定晶格结构,提高材料的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419245B_ABST
    Figure CN119419245B_ABST
Patent Text Reader

Abstract

The application relates to the field of sodium ion battery positive electrode materials, in particular to an rGO-coated Mn-Ti co-doped fluorinated sodium iron phosphate material and a preparation method and application thereof; the chemical formula is Na2Fe x Mn y Ti z PO4F@rGO; wherein 0.05<=y<=0.10, 0.02<=z<=0.05, and x+y+z=1; the application is characterized in that: by optimizing the raw material proportion, sintering conditions, and adopting a two-time sintering process of low-temperature pre-sintering-ball milling under inert atmosphere-second sintering, the raw materials are uniformly mixed and the contact area is increased under the premise that the raw materials are not oxidized and deteriorated by air, which is beneficial to efficient ion migration and lattice formation between reactants, the strong electronegative anion F is successfully introduced, a strong binding force is formed with a phosphate group, the generation of pyrophosphoric acid is inhibited, and the crystal structure is optimized; by Mn-Ti co-doping, the voltage platform and material structure stability are effectively improved, the material has a high energy density and a long cycle life; meanwhile, the two-dimensional rGO coating can also form a stable interface layer on the material surface, reduces the occurrence of interface side reactions, and improves the cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cathode materials for sodium-ion batteries, and more particularly to an rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material, its preparation method, and its application. Background Technology

[0002] With the depletion of traditional fossil fuels, various new renewable energy sources have broad application prospects. Among them, sodium-ion batteries, as an emerging rechargeable battery, have advantages such as abundant resources, low price, and good safety. Their key technologies are not significantly different from lithium-ion batteries, providing a solid technological foundation. Furthermore, sodium-ion batteries can achieve wide-temperature discharge and rapid charge-discharge, making them a primary choice for large-scale energy storage power stations with relatively lower energy density requirements.

[0003] Polyanionic cathode materials have become a research hotspot in the field of sodium-ion battery cathode materials due to their three-dimensional structure, low cost, and high safety. However, commonly used sodium-ion battery cathode materials still face many challenges, such as low energy density and poor cycle performance. For example, Chinese patent document CN116565180A discloses a method for surface coating of lithium-ion battery cathode powder materials, involving a method for preparing carbon coating on the surface of lithium iron phosphate materials. Although compared to lithium iron phosphate materials, sodium iron phosphate fluoride materials contain Na+ with a larger ionic radius... + And F, which has stronger electronegativity - However, sodium iron phosphate fluoride has poor structural stability, low intrinsic electronic conductivity, and poor mechanical properties. Applying the same processing conditions used for lithium iron phosphate materials directly to sodium iron phosphate fluoride can easily lead to cracking and other problems, thus affecting material performance. Chinese patent document CN116169264A discloses a carbon-coated sodium-rich pyrophosphate sodium iron phosphate composite cathode material, its preparation method, and its application. Although this is a new material applicable to sodium-ion batteries, pyrophosphate has low electronic conductivity and is prone to structural changes during charge-discharge cycles, leading to a decrease in battery voltage plateau and overall specific capacity. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies by providing an rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material, its preparation method, and its application, which can further improve the energy density and cycle performance of cathode materials.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] The first aspect of this invention is to provide an rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material with the chemical formula Na₂Fe₂O₃. x Mn y Ti zPO4F@rGO; where 0.05≤y≤0.10, 0.02≤z≤0.05, x+y+z=1; Fe is +2 valence, Mn is +2 valence, and Ti is +2 valence.

[0007] A second aspect of the present invention is to provide a method for preparing the above-mentioned rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material, the steps of which include:

[0008] S1. After mixing sodium source, iron source, manganese source, titanium source, phosphorus source and fluorine source in proportion, the mixture is subjected to first ball milling treatment, first drying treatment and pre-sintering treatment in sequence to obtain the first calcination product.

[0009] S2. The first calcination product is subjected to a second ball milling treatment, a second drying treatment, and a second sintering treatment in sequence to obtain the Mn-Ti co-doped sodium fluorinated phosphate material.

[0010] S3. Disperse the Mn-Ti co-doped sodium fluorinated phosphate material in anhydrous ethanol and sonicate it to obtain a suspension.

[0011] S4. The rGO dispersion is added dropwise to the suspension while stirring continuously. Then, hydrothermal treatment, washing treatment and third drying treatment are performed in sequence to obtain the rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material.

[0012] Preferably, in step S1, the molar ratio of sodium, iron, manganese, titanium, phosphorus and fluorine in the mixture is 2:x:y:z:1:1.

[0013] Preferably, in step S1, the sodium source includes at least one of sodium fluoride, sodium acetate, sodium carbonate, sodium citrate, and sodium oxalate.

[0014] The iron source includes at least one of ferrous oxalate, ferrous sulfate, and ferrous chloride.

[0015] The manganese source includes at least one of manganese dioxide, manganese trioxide, and manganese oxalate.

[0016] The titanium source includes at least one of titanium monoxide, titanium dioxide, titanium oxalate, and titanium sulfate.

[0017] The phosphorus source includes at least one of: ammonium dihydrogen phosphate and diammonium hydrogen phosphate;

[0018] The fluorine source includes at least one of sodium fluoride and hydrofluoric acid.

[0019] Preferably, in step S1, the rotation speed of the first ball milling treatment is 300-500 rpm, and the time is 6-8 h; the mass ratio of the milling beads to the mixture is (8-10):1;

[0020] The temperature of the first drying process is 60-100℃, and the time is 8-14 hours.

[0021] Preferably, in step S1, the pre-sintering treatment includes: pre-purifying with protective gas at room temperature for 0.5-2 hours, heating from room temperature to 350-450°C at a rate of 3-5°C / min, and calcining for 2-6 hours;

[0022] The protective gas is at least one of argon, hydrogen-argon, nitrogen, and helium.

[0023] Preferably, in step S2, the rotation speed of the second ball milling treatment is 400-500 rpm, and the time is 4-6 h; the mass ratio of the ball milling beads to the first calcined product is (8-10):1.

[0024] The second drying process is carried out at a temperature of 60-100℃ for 8-14 hours.

[0025] Preferably, in step S2, the secondary sintering treatment includes: pre-purifying with protective gas at room temperature for 0.5-2 hours, heating from room temperature to 550-650°C at a rate of 3-5°C / min, and calcining for 8-12 hours;

[0026] The protective gas is at least one of argon, hydrogen-argon, nitrogen, and helium.

[0027] Preferably, in step S4, the mass ratio of the Mn-Ti co-doped sodium fluorinated phosphate material to rGO is 1:(0.005-0.01);

[0028] The hydrothermal treatment temperature is 120-140℃; the reaction time is 6-8h.

[0029] A third aspect of the present invention is to provide the application of the above-described rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material or the rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material prepared by the above preparation method in the cathode material of sodium-ion batteries.

[0030] The present invention adopts the above technical solution and has the following technical effects compared with the prior art:

[0031] (1) This invention improves the electronic conductivity of phosphate materials by Mn-Ti co-doping and rGO coating on Na2FePO4F materials, while enhancing the structural stability of the materials, so that the positive electrode active materials have both high energy density and cycle stability. Among them, manganese doping can effectively improve the energy density of the materials and can be anchored between the crystal lattice to widen the lattice size and improve the sodium ion transport rate. Low-valence titanium doping can stabilize the crystal structure and improve the cycle stability of the materials.

[0032] (2) By combining ball milling, sintering and hydrothermal reaction, the present invention can better coordinate the coating thickness to take into account both electronic conductivity and specific capacity, and suppress the generation of cracks caused by material volume changes during cycling. It forms a uniform rGO coating on the material surface, reduces the interfacial side reactions between the material and the electrolyte, and improves the problems of low discharge capacity and poor rate performance caused by the low conductivity of the material itself.

[0033] (3) This invention optimizes the raw material ratio and sintering conditions, and adopts a two-stage sintering process of low-temperature pre-sintering-ball milling under an inert atmosphere-secondary sintering, so that the raw materials are uniformly mixed and the contact area is increased without being oxidized or deteriorated by air. This is conducive to efficient ion migration and lattice formation between reactants, and successfully introduces the strongly electronegative anion F, which forms a strong binding force with the phosphate group, inhibits the formation of pyrophosphate, and optimizes the crystal structure. Na2FePO4F, as a polyanionic compound, has a narrow and stable charge-discharge curve, and the battery management is relatively easy, making it suitable for large-scale grid energy storage. Through Mn-Ti co-doping, the voltage plateau and material structure stability are effectively improved, so that the material has a high energy density and a long cycle life. At the same time, the two-dimensional rGO coating, in addition to improving the conductivity, can also form a stable interface layer on the material surface, reduce the occurrence of interface side reactions, and improve cycle stability. Attached Figure Description

[0034] Figure 1 The rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material Na2Fe prepared in Example 1 of this invention 0.85 Mn 0.1 Ti 0.05 XRD pattern of PO4F@rGO;

[0035] Figure 2 The rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material Na2Fe prepared in Example 1 of this invention 0.85 Mn 0.1 Ti 0.05 SEM image of PO4F@rGO;

[0036] Figure 3 The rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material Na2Fe prepared in Example 1 of this invention 0.85 Mn 0.1 Ti 0.05 Comparison of charge-discharge curves of PO4F@rGO and undoped Na2FePO4F. Detailed Implementation

[0037] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.

[0039] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the scope of the invention.

[0040] Example 1

[0041] This embodiment provides an rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material Na2Fe 0.85 Mn 0.1 Ti 0.05 The preparation method of PO4F@rGO includes the following steps:

[0042] S1. Sodium acetate, ferrous oxalate, manganese oxalate, titanium oxalate, diammonium hydrogen phosphate, and sodium fluoride are mixed in a molar ratio of 1:0.85:0.1:0.05:1:1. The mixture is then subjected to a first ball milling treatment, a first drying treatment, and a pre-sintering treatment to obtain a first-calcined product. The molar ratio of sodium, iron, manganese, titanium, phosphorus, and fluorine in the mixture is 2:0.85:0.1:0.05:1:1. The first ball milling treatment is performed at a speed of 500 rpm for 6 hours. The mass ratio of the milling beads to the mixture is 8:1. The first drying treatment is performed at a temperature of 60°C for 14 hours. The pre-sintering treatment includes: pre-purifying with argon gas at room temperature for 1 hour, then heating from room temperature to 350°C at a rate of 3°C / min, and calcining for 6 hours.

[0043] S2. The first calcined product is subjected to a second ball milling treatment, a second drying treatment, and a second sintering treatment to obtain the Mn-Ti co-doped sodium fluorinated phosphate material. The second ball milling treatment is performed at a speed of 500 rpm for 4 hours. The mass ratio of the ball milling beads to the first calcined product is 8:1. The second drying treatment is performed at a temperature of 60°C for 14 hours. The second sintering treatment includes: pre-purifying with argon gas at room temperature for 1 hour, then heating from room temperature to 550°C at a rate of 3°C / min, and calcining for 12 hours.

[0044] S3. Disperse the Mn-Ti co-doped sodium fluorinated phosphate material in anhydrous ethanol and sonicate it to obtain a suspension.

[0045] S4. The rGO dispersion is added dropwise to the suspension (the mass ratio of Mn-Ti co-doped sodium fluorinated iron phosphate material to rGO is 1:0.005) while stirring continuously. Then, hydrothermal treatment, washing, and a third drying treatment are performed sequentially to obtain the rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material Na2Fe. 0.85 Mn 0.1 Ti 0.05 PO4F@rGO; the hydrothermal treatment temperature is 120℃; the reaction time is 8h.

[0046] Example 2

[0047] This embodiment provides another rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material, Na2Fe. 0.88 Mn 0.08 Ti 0.04 The preparation method of PO4F@rGO includes the following steps:

[0048] S1. Sodium acetate, ferrous chloride, manganese trioxide, titanium dioxide, diammonium hydrogen phosphate, and sodium fluoride are mixed in a molar ratio of 1:0.88:0.04:0.04:1:1. The mixture is then subjected to a first ball milling treatment, a first drying treatment, and a pre-sintering treatment to obtain a first-calcination product. The molar ratio of sodium, iron, manganese, titanium, phosphorus, and fluorine in the mixture is 2:0.88:0.08:0.04:1:1. The first ball milling treatment is performed at a speed of 300 rpm for 8 hours. The mass ratio of the milling beads to the mixture is 9:1. The first drying treatment is performed at a temperature of 80°C for 12 hours. The pre-sintering treatment includes: pre-purifying with hydrogen and argon gas at room temperature for 1.5 hours, then heating from room temperature to 400°C at a rate of 4°C / min, and calcining for 4 hours.

[0049] S2. The first calcined product is subjected to a second ball milling treatment, a second drying treatment, and a second sintering treatment to obtain the Mn-Ti co-doped sodium iron fluoride phosphate material. The second ball milling treatment is performed at a speed of 400 rpm for 6 hours. The mass ratio of the ball milling beads to the first calcined product is 9:1. The second drying treatment is performed at a temperature of 80°C for 12 hours. The second sintering treatment includes: pre-purifying with hydrogen and argon gas at room temperature for 1.5 hours, then heating from room temperature to 600°C at a rate of 4°C / min, and calcining for 10 hours.

[0050] S3. Disperse the Mn-Ti co-doped sodium fluorinated phosphate material in anhydrous ethanol and sonicate it to obtain a suspension.

[0051] S4. The rGO dispersion is added dropwise to the suspension (the mass ratio of Mn-Ti co-doped sodium fluorinated iron phosphate material to rGO is 1:0.008) while stirring continuously. Then, hydrothermal treatment, washing, and a third drying treatment are performed sequentially to obtain the rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material Na2Fe. 0.88 Mn 0.08 Ti 0.04 PO4F@rGO; the hydrothermal treatment temperature is 130℃; the reaction time is 7h.

[0052] Example 3

[0053] This embodiment provides another rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material, Na2Fe. 0.93 Mn 0.05 Ti 0.02 The preparation method of PO4F@rGO includes the following steps:

[0054] S1. Sodium acetate, ferrous sulfate, manganese dioxide, titanium dioxide, diammonium hydrogen phosphate, and sodium fluoride are mixed in a molar ratio of 1:0.93:0.05:0.02:1:1. The mixture is then subjected to a first ball milling treatment, a first drying treatment, and a pre-sintering treatment to obtain a first-calcined product. The molar ratio of sodium, iron, manganese, titanium, phosphorus, and fluorine in the mixture is 2:0.93:0.05:0.02:1:1. The first ball milling treatment is performed at a speed of 400 rpm for 7 hours. The mass ratio of the milling beads to the mixture is 10:1. The first drying treatment is performed at a temperature of 100°C for 10 hours. The pre-sintering treatment includes: pre-purging with nitrogen at room temperature for 2 hours, then heating from room temperature to 450°C at a rate of 5°C / min, and calcining for 3 hours.

[0055] S2. The first calcined product is subjected to a second ball milling treatment, a second drying treatment, and a second sintering treatment to obtain the Mn-Ti co-doped sodium fluorinated iron phosphate material. The second ball milling treatment is performed at a speed of 450 rpm for 5 hours. The mass ratio of the ball milling beads to the first calcined product is 10:1. The second drying treatment is performed at a temperature of 100°C for 10 hours. The second sintering treatment includes: pre-purging nitrogen at room temperature for 2 hours, then heating from room temperature to 650°C at a rate of 5°C / min, and calcining for 8 hours.

[0056] S3. Disperse the Mn-Ti co-doped sodium fluorinated phosphate material in anhydrous ethanol and sonicate it to obtain a suspension.

[0057] S4. The rGO dispersion is added dropwise to the suspension (the mass ratio of Mn-Ti co-doped sodium fluorinated iron phosphate material to rGO is 1:0.01) while stirring continuously. Then, hydrothermal treatment, washing, and a third drying treatment are performed sequentially to obtain the rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material Na2Fe. 0.93 Mn 0.05 Ti 0.02 PO4F@rGO; the hydrothermal treatment temperature is 140℃; the reaction time is 6h.

[0058] Comparative Example 1

[0059] This comparative example provides another sodium ferric fluoride phosphate material, which is not coated with rGO compared to Example 1, but otherwise is the same as Example 1.

[0060] Comparative Example 2

[0061] This comparative example provides another sodium ferric fluoride phosphate material, which is prepared using a conventional one-time sintering method, and all other aspects are the same as in Example 1.

[0062] Comparative Example 3

[0063] This comparative example provides another sodium fluorinated phosphate material, which is prepared without Mn or Ti doping, and otherwise identical to Example 1.

[0064] Detection Examples

[0065] 1. Morphological test

[0066] SEM is the most basic testing method for observing the microstructure of materials. A ZEISS GEMINI 500 scanning electron microscope (Germany) was used to examine the Na₂Fe₂ prepared by the method described in Example 1. 0.85 Mn 0.1 Ti 0.05 The surface morphology of PO4F@rGO was characterized. To improve the conductivity of the material and obtain clearer scanning images, the material was sputter-coated with gold before testing.

[0067] The results are as follows Figure 2 As shown, Na2Fe 0.85 Mn 0.1 Ti 0.05 PO4F@rGO consists of spherical particles with a diameter of 2-3 μm and a highly fluffy, unique morphology.

[0068] 2. Battery cycle performance testing

[0069] To test the electrochemical performance of the materials, half-cells were assembled using the materials from Examples 1-3 and Comparative Examples 1-3 as positive electrodes, respectively, and their electrochemical performance was tested. First, 175 mg of the material and 50 mg of SuperP were weighed and ground in an agate mortar for approximately 20 minutes until thoroughly mixed. The mixture was then transferred to a paste bottle, and 500 mg of a pre-prepared 5 wt% VDF NMP solution was added, followed by approximately 800 μL of NMP solution. The mixture was magnetically stirred for approximately 12 hours until a slightly viscous paste-like liquid was formed. Subsequently, a 120 μm spatula was used to evenly coat the paste onto an aluminum foil, and the mixture was vacuum dried at 120°C for 12 hours. The resulting positive electrode sheet was then formed into a 12 mm diameter positive electrode sheet using a die-cutting machine. Using this electrode sheet as the positive electrode, a sodium sheet as the negative electrode, and glass fiber as the separator, a 1.0 M NaClO4 / EC-PC electrolyte (volume ratio 1:1, 5.0 vol% FEC) was selected. CR2032 coin cells were assembled in an argon-filled glove box. The coin cell battery was subjected to constant current charge-discharge at 0.2C (1C = 120 mAh / g), with a voltage range of 2.0-4.0V. A comparison of its charge-discharge curve with that of undoped Na₂FePO₄F is shown below. Figure 3 As shown in the figure; the charging and discharging results are shown in Table 1.

[0070] Table 1

[0071]

[0072] Compared to cathode materials without rGO coating (Comparative Example 1), those using a single sintering method (Comparative Example 2), and those without Mn and Ti doping (Comparative Example 3), this invention improves the electronic conductivity of phosphate materials by co-doping Na2FePO4F materials with Mn-Ti, while also enhancing the structural stability of the materials. This results in cathode active materials with both high energy density and cycle stability. Specifically, manganese doping effectively increases the energy density of the material and can anchor between crystal lattice layers to widen the lattice size, thereby increasing the sodium ion transport rate. Low-valence titanium doping stabilizes the crystal structure and improves the cycle stability of the material. The combination of two ball milling processes, sintering, and hydrothermal reaction ensures uniform mixing of raw materials without oxidation or deterioration by air, increasing the contact area and facilitating efficient ion migration and lattice formation between reactants. This allows even less reactive F atoms to form stable chemical bonds, creating strong bonds with phosphate groups, inhibiting the formation of pyrophosphate, and improving the purity and crystallinity of the material. It also enables two-dimensional rGO coating on the material surface, which not only improves electrical conductivity but also forms a stable interface layer on the material surface, reducing the occurrence of interface side reactions and improving cycle stability.

[0073] The above description is merely a preferred embodiment of the present invention and does not limit the implementation and protection scope of the present invention. Those skilled in the art should realize that any equivalent substitutions and obvious changes made based on the description and illustrations of the present invention should be included within the protection scope of the present invention.

Claims

1. A rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material, characterized in that, The chemical formula is Na2Fe x Mn y Ti z PO4F@rGO; where 0.05≤y≤0.10, 0.02≤z≤0.05, x+y+z=1; Fe is +2 valence, Mn is +2 valence, Ti is +2 valence; the Mn-Ti co-doped sodium iron fluoride phosphate material coated by rGO is a spherical particle with a high-fluffy special morphology and a diameter of 2-3μm; Preparation methods include: S1. After mixing sodium source, iron source, manganese source, titanium source, phosphorus source and fluorine source in proportion, the mixture is subjected to first ball milling treatment, first drying treatment and pre-sintering treatment in sequence to obtain the first calcination product. S2. The first calcination product is subjected to a second ball milling treatment, a second drying treatment, and a second sintering treatment in sequence to obtain the Mn-Ti co-doped sodium fluorinated phosphate material. S3. Disperse the Mn-Ti co-doped sodium fluorinated phosphate material in anhydrous ethanol and sonicate it to obtain a suspension. S4. The rGO dispersion is added dropwise to the suspension while stirring continuously. Then, hydrothermal treatment, washing treatment and third drying treatment are performed in sequence to obtain the rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material. The above preparation method inhibited the formation of pyrophosphate.

2. A method for preparing rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material as described in claim 1, characterized in that the step... include: S1. After mixing sodium source, iron source, manganese source, titanium source, phosphorus source and fluorine source in proportion, the mixture is subjected to first ball milling treatment, first drying treatment and pre-sintering treatment in sequence to obtain the first calcination product. S2. The first calcination product is subjected to a second ball milling treatment, a second drying treatment, and a second sintering treatment in sequence to obtain the Mn-Ti co-doped sodium fluorinated phosphate material. S3. Disperse the Mn-Ti co-doped sodium fluorinated phosphate material in anhydrous ethanol and sonicate it to obtain a suspension. S4. The rGO dispersion is added dropwise to the suspension while stirring continuously. Then, hydrothermal treatment, washing treatment and third drying treatment are performed in sequence to obtain the rGO-coated Mn-Ti co-doped sodium fluorinated phosphate material.

3. The preparation method according to claim 2, characterized in that, In step S1, the sodium source includes at least one of sodium fluoride, sodium acetate, sodium carbonate, sodium citrate, and sodium oxalate. The iron source includes at least one of ferrous oxalate, ferrous sulfate, and ferrous chloride. The manganese source includes at least one of manganese dioxide, manganese trioxide, and manganese oxalate. The titanium source includes at least one of titanium monoxide, titanium dioxide, titanium oxalate, and titanium sulfate. The phosphorus source includes at least one of: ammonium dihydrogen phosphate and diammonium hydrogen phosphate; The fluorine source includes at least one of sodium fluoride and hydrofluoric acid.

4. The preparation method according to claim 2, characterized in that, In step S1, the first ball milling process is performed at a speed of 300-500 rpm for 6-8 hours; the mass ratio of the milling balls to the mixture is (8-10):

1. The temperature of the first drying process is 60-100℃, and the time is 8-14 hours.

5. The preparation method according to claim 2, characterized in that, In step S1, the pre-sintering treatment includes: pre-purifying with protective gas at room temperature for 0.5-2 hours, heating from room temperature to 350-450°C at a rate of 3-5°C / min, and calcining for 2-6 hours; The protective gas is at least one of argon, hydrogen-argon, nitrogen, and helium.

6. The preparation method according to claim 2, characterized in that, In step S2, the second ball milling process is performed at a speed of 400-500 rpm for 4-6 hours; the mass ratio of the ball milling beads to the first calcined product is (8-10):

1. The second drying process is carried out at a temperature of 60-100℃ for 8-14 hours.

7. The preparation method according to claim 2, characterized in that, In step S2, the secondary sintering treatment includes: pre-purifying with protective gas at room temperature for 0.5-2 hours, heating from room temperature to 550-650°C at a rate of 3-5°C / min, and calcining for 8-12 hours; The protective gas is at least one of argon, hydrogen-argon, nitrogen, and helium.

8. The preparation method according to claim 2, characterized in that, In step S4, the mass ratio of the Mn-Ti co-doped sodium fluorinated phosphate material to rGO is 1:(0.005-0.01). The hydrothermal treatment temperature is 120-140℃; the reaction time is 6-8h.

9. The application of the rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material as described in claim 1 or the rGO-coated Mn-Ti co-doped sodium fluorinated iron phosphate material prepared by any one of the preparation methods described in claims 2-8 in the cathode material of sodium-ion batteries.

Citation Information

Patent Citations

  • High-tap-density lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN116565180A

  • Carbon-coated sodium ferric fluorophosphate material as well as preparation method and application thereof

    CN114242968A

  • Carbon-coated sodium-rich sodium ferric pyrophosphate composite positive electrode material, preparation method and application

    CN116169264A